The Influence of Work from Home on Work-Life Balance and Job Satisfaction Among Generation Z Employees in Bandung - Mohammed Magistra Avicenna; Kiki Sudiana (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The rise of remote work has reshaped how employees balance their professional and personal lives, especially among younger generations who value flexibility. This study aims to examine the influence of work from home on work-life balance and job satisfaction among Generation Z employees in Bandung, Indonesia, where technology-driven industries have rapidly adopted flexible work arrangements. A quantitative approach was used, collecting data through questionnaires distributed to 385 Generation Z respondents who have worked remotely in Bandung’s technology and creative industries. The variables measured include work from home as the independent variable, and work–life balance and job satisfaction as dependent variables. Data were analyzed using structural equation modeling with SmartPLS software to ensure robust estimation of the proposed relationships. The findings show that work from home has a significant positive impact on work-life balance and job satisfaction. Despite its geographical and generational scope, this study suggests that organizations should design effective remote work policies to boost productivity and well-being, contributing to better employee outcomes in tech-driven environments.